1631 The Pen is Mightier than the Sword; but the Keyboard may be Better. (12th October 2021) - Morrison, S; Brunt, A
Abstract: Introduction: Operation notes ensure patient safety through continuity of care, and act as reliable treatment records. Notes must be legible, accessible, and contain all relevant information. Specific standards are outlined in the Good Surgical Practice Guidelines (2014) by the Royal College of Surgeons of England. Audits in the UK show poor adherence to these standards. Online operative note systems are becoming more common, but variety still exists in operations notes. This work assessed operative note standards in an orthopaedic department and assessed the utility of electronic operative note systems. Method: This was a prospective quality improvement project. Operation notes for all emergency orthopaedic operations were audited against national standards. An online operation note system was introduced and re-audit carried out following implementation. Results: Initial audit noted poor adherence to standards. An online operative note system was introduced. A second audit with 96 patients was undertaken. Uptake of the software was low, with 10% of notes being online. 19 of 21 information points showed improved standards adherence with the online system versus other methods. In the remaining 2 areas 100% of notes adhered to standards in both methods. The online system had 100% adherence in 19 data points, and 90% in the remaining 2. Conclusions: Online note softwares have various benefits, including improved adherence to standards. Other benefits exist, such as databasing of operations for review and audit. These systems appear reliable and beneficial for operative documentation and are easily implemented; however, some work is still required to change old habits and improve uptake.